Climate variability and agricultural production in Argentina: the role of risk-transfer mechanisms - Gallacher, Marcos; Lema, Rolando Daniel; Galetto, Alejandro J.; Gastaldi, Laura Beatriz (UCEMA, 2025)
Research related to climate variability is particularly important in the current conditions faced by Argentine agriculture. These include (a) increased specialization in soybeans, with resulting reduced possibilities of risk-reduction though "portfolio" effects, (b) increased importance of agriculture in "non-traditional" areas, generally characterized by lower yields, higher yield variability and higher production and transport costs, (c) macroeconomic instability resulting in severe contraction and increased interest rates of credit and (d) upward trend in input use and per-acre production costs with consequent increase in break-even crop yields. This paper summarize recent research related to production variability in Argentine agriculture, as well as the consequences of this variability on efficiency and resource allocation and present an overview of strategies for coping with climate variability. We estimate possible benefits to agricultural producers of improved risk-transfer mechanisms. In particular, we obtain estimates of Willingness-to-Pay (WTP) of selected index-type insurance mechanisms for soybean and milk production and outline the requirements for the development of a risk-transfer market for agricultural producers.